Combinatorial Tim‐3 and PD‐1 activity sustains antigen‐specific Th1 cell numbers during blood‐stage malaria. (25th May 2020) - Dookie, Rebecca S.; Villegas‐Mendez, Ana; Kroeze, Hans; Barrett, Jordan R.; Draper, Simon J.; Franke‐Fayard, Blandine M.; Janse, Chris J.; MacDonald, Andrew S.; Couper, Kevin N.
Abstract: Aims: Co‐inhibitory receptors play a major role in controlling the Th1 response during blood‐stage malaria. Whilst PD‐1 is viewed as the dominant co‐inhibitory receptor restricting T cell responses, the roles of other such receptors in coordinating Th1 cell activity during malaria are poorly understood. Methods and Results: Here, we show that the co‐inhibitory receptor Tim‐3 is expressed on splenic antigen‐specific T‐bet + (Th1) OT‐II cells transiently during the early stage of infection with transgenic Plasmodium yoelii NL parasites expressing ovalbumin ( P yoelii NL‐ OVA) . We reveal that co‐blockade of Tim‐3 and PD‐L1 during the acute phase of P yoelii NL infection did not improve the Th1 cell response but instead led to a specific reduction in the numbers of splenic Th1 OT‐II cells. Combined blockade of Tim‐3 and PD‐L1 did elevate anti‐parasite IgG antibody responses. Nevertheless, co‐blockade of Tim‐3 and PD‐L1 did not affect IFN‐γ production by OT‐II cells and did not influence parasite control during P yoelii NL‐ OVA infection. Conclusion: Thus, our results show that Tim‐3 plays an unexpected combinatorial role with PD‐1 in promoting and/ or sustaining a Th1 cell response during the early phase of blood‐stage P. yoel ii NL infection but combined blockade does not dramatically influence anti‐parasite immunity.